Physical properties of nanomaterials - Čitaković, Nada M. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Nanotechnology deals with the creation of materials, devices and systems through manipulation of matter at the nanometer length scale. The created object itself does not have to be a nanoscale size object, it might be a micro or macro size object. Significant changes have been observed in physical, chemical, mechanical, electrical, optical, magnetic, and other properties when going down from bulk to nanoscale materials.
Keywords: nanotechnology; nanomaterials; nanoparticles; properties of nanomaterials